Answer with Explanation:
Given that
![x(t)=x_ocos(\gamma t)............(i)](https://img.qammunity.org/2020/formulas/engineering/college/mgcc14ktcwub2uwd5szrt9bp73r42nhzu6.png)
![y(t)=y_osin(\gamma t)..............(ii)](https://img.qammunity.org/2020/formulas/engineering/college/mm636hn78uaubbsyff9v2c0p05k4nebv66.png)
Thus by definition x component of velocity in Lagrangian system is given by
![u=(dx)/(dt)\\\\u=(d(x_ocos(\gamma t))/(dt)=-\gamma x_osin(\gamma t)](https://img.qammunity.org/2020/formulas/engineering/college/s6oqtbsxok84vpp6a6uk0i5wikdd6wljhm.png)
Thus by definition y component of velocity in Lagrangian system is given by
![v=(dy)/(dt)\\\\v=(d(y_osin(\gamma t))/(dt)=\gamma y_ocos(\gamma t)](https://img.qammunity.org/2020/formulas/engineering/college/rcod8fw0wbub8cpjqc770wlb6ioudmnrcw.png)
Since in eulerian system we need to eliminate time from the equations
From euations 'i' and 'ii' we can write
![cos(\gamma t)=(x)/(x_o)\\\\sin(\gamma t)=(y)/(y_o)](https://img.qammunity.org/2020/formulas/engineering/college/t86w6on3e9tq0o5io0rby6gvkmiftyr1mi.png)
Applying these values in the velocity components as obtained in Lagrangian system we get
![u=(-\gamma x_o)/(y_o)\cdot y\\\\v=(\gamma y_o)/(x_o)\cdot x](https://img.qammunity.org/2020/formulas/engineering/college/il47mtkb86p9svc4szaflxmhp7hpr09uci.png)